Das Michelangelo-Phänomen – Relationale Führungskompetenz für das Gesundheitswesen der (digitalen) Zukunft - Junne, Florian; Zipfel, Stephan (PPmP - Psychotherapie · Psychosomatik · Medizinische Psychologie, 2019)
„In the past jobs were about muscles, now they are about the brain, in the future they will be about the heart.“Dame Minouche Shafik, Director of the London School of Economics (LSE) (2018)